Nutritional and health impact of substituting Greengram by Soya products in School lunch Programme in Thrissur District - Latha Devi N (Department of Home Science, College of Horticulture, 2000)
The present study, entitled 'Nutritional and health impact of substituting green gram by soya products in school lunch programme in Thrissur district' was conducted among 150 school children, who were randomly selected, 50 each from three groups VIZ., soya supplemented lunch (SSL), existing school lunch (ESL) and no school lunch (NSL). The socio-economic details inferred through the survey were found to be satisfactory. Nuclear families with better housing facilities and good educational level wmthe striking features observed. Most of the fathers were casual labourers. Monthly income in most of the families was up to Rs.2000 in all groups. Most of the families owned their own houses. Food consumption survey revealed that all were habitual non- vegetarians. Cereals, other vegetables, fats and oils and sugar and jaggery were the most frequently used food items. Dietary profile of school children revealed that intake of all the food items, except green leafy vegetables met the daily requirement and all the nutrients except thiamine and riboflavin were above the RDA in all the groups. Majority of the mothers were having positive opinion about the school lunch programme. Most of the teachers opined that except for food materials, no other financial support for school lunch programme is obtained from the government. Evaluation of defatted soya products at different replacement levels with green gram showed that, soya grits at 20 per cent replacement level was the most acceptable combination in terms of organoleptic and nutritive qualities. Assessment of nutritional status after the study period revealed that, significant difference existed between the three groups with regard to body weight,